Artificial Intelligence and Digital Literacy for Competitiveness and Sustainability of Bandung MSMEs - Istikomah Istikomah; Afrizal Maulana; Susilawati Susilawati; Yoki Muchsam (Information Technology and Science (ITScience), 2026)
This research aims to analyze the role of artificial intelligence (AI) in digital marketing and digital literacy on the competitiveness and sustainability of micro, small, and medium enterprises (MSMEs) in Bandung City during the platform economy era. The development of digital technology opens up great opportunities for MSMEs, but low digital literacy and limited utilization of AI still pose obstacles to increasing competitiveness. The research method uses a mixed methods approach with a survey of 150 MSME owners and in-depth interviews with some respondents. The sample selection was done purposively, while the quantitative data was analyzed using Structural Equation Modeling (SmartPLS 4) and the qualitative data was used for triangulation. The research results indicate that the adoption of AI in digital marketing and digital literacy has a significant positive impact on the competitiveness of MSMEs. Stronger competitiveness is proven to support business sustainability. Additionally, digital literacy serves as a mediator that strengthens the effectiveness of AI-based marketing strategies. This research confirms that improving digital literacy and utilizing AI are crucial strategies for SMEs in facing the challenges of the platform economy. The research results are expected to contribute to the development of policies, business strategies, and academic literature related to the digital transformation of MSMEs in Indonesia.